Presidential Address: Social Transmission Bias in Economics and Finance - HIRSHLEIFER, DAVID (Journal of Finance, 2020)
ABSTRACT I discuss a new intellectual paradigm, social economics and finance —the study of the social processes that shape economic thinking and behavior. This emerging field recognizes that people observe and talk to each other. A key, underexploited building block of social economics and finance is social transmission bias : systematic directional shift in signals or ideas induced by social transactions. I use five “fables” (models) to illustrate the novelty and scope of the transmission bias approach, and offer several emergent themes. For example, social transmission bias compounds recursively, which can help explain booms, bubbles, return anomalies, and swings in economic sentiment.